The impact of digital media on the development of critical thinking skills among middle school students: A field study (The International Journal for Scientific Research, 2024)
This study aimed to measure the impact of digital media on the development of critical thinking skills among middle school students, by analyzing how middle school students use digital media and its impact on their ability to think critically, including evaluating and deriving information, and the study followed the descriptive survey approach and the study sample consisted of (157) male and female students in the intermediate stage from schools in the Jazan region in the Kingdom of Saudi Arabia, and the results of the current study show that there are no statistically significant differences between sex Or age in the impact of digital media on the development of critical thinking skills among middle school students. The ANOVA test was used to check for these differences, and the p-value values for sex (0.780) and age (0.333) were higher than the significance level of 0.05, suggesting that there was no significant effect of these two variables on critical thinking skills as measured in this study. The study recommends the development of educational programs that focus on enhancing critical thinking skills among middle school students through the use of digital media. These programs should include guiding students on how to verify information and distinguish true news from false news.
Keywords: Digital Media; Critical Thinking; Middle School